KORELASI ANTARA LINGKAR DADA, PANJANG BADAN DAN TINGGI GUMBA TERHADAP VOLUME SEMEN DAN KONSENTRASI SPERMATOZOA SAPI MADURA - Mayola, Dilla Aranda; Rimayanti, Rimayanti; Warsito, Sunaryo Hadi; Utama, Suzanita; Eliyani, Hana; Safitri, Erma (Universitas Airlangga, 2019)
The aim of this research was to know the correlation between heart girth, body length, and wither's height with semen volume and sperm concentration of Madura Bulls. Ten Madura bulls aged three to four years from Madura were measured. Variables observed were heart girth, body length, wither's height, semen volume and sperm concentration. Data were analyzed by multiple linear regression analysis. The result of this research showed that there was no correlation between heart girth, body length, and wither's height with semen volume Y = 25,212 + 0,190 X1+ (-0,131) X2 + 0,136 X3, so as there was no correlation between heart girth, body length and wither's height with sperm concentration Y = 8739,559 + (-36,663) X1+ (19,714) X2 + 6,2960 X3. And than was no correlation between semen volume and sperm concentration Y = 7,303 + (-0,002) X1.